2017
DOI: 10.1044/2017_ajslp-16-0173
|View full text |Cite
|
Sign up to set email alerts
|

South Asian Adults' Performance on Executive Function Tests

Abstract: Performance differences on EF tests may exist between South Asian and White adults. Further research is necessary to determine the impact of cultural and linguistic differences on EF test performance in South Asian adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Therefore, it is difficult to say if participants who were not as highly educated would have had similar outcomes. Also, recent studies have reported that adults representing CLD populations have had differing performance on the BADS and FA-VRES compared to Caucasian adults [27,42]. It is unknown if the current study's results would have differed had there been a greater number of persons representing CLD populations.…”
Section: Limitations and Future Researchmentioning
confidence: 72%
See 2 more Smart Citations
“…Therefore, it is difficult to say if participants who were not as highly educated would have had similar outcomes. Also, recent studies have reported that adults representing CLD populations have had differing performance on the BADS and FA-VRES compared to Caucasian adults [27,42]. It is unknown if the current study's results would have differed had there been a greater number of persons representing CLD populations.…”
Section: Limitations and Future Researchmentioning
confidence: 72%
“…Data analysis of the BADS and the FAVRES followed the format used in previous studies [21,27,31]. Raw scores on the BADS were converted to Profile Scores that ranged from 0 to 4.…”
Section: Stimuli Procedures and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Tests used in the current study have been described in previous studies [13,[29][30][31]. The Attention Process Training Test (APT-Test) evaluates simple sustained, complex sustained, se-lective, divided, and alternating attention [32].…”
Section: Introductionmentioning
confidence: 99%
“…Both EF tests used in the current study have also been described by researchers [13,29,31]. The Behavioural Assessment of the Dysexecutive Syndrome (BADS) [33] includes six tests (i.e., subtests) to assess EF abilities.…”
Section: Introductionmentioning
confidence: 99%